A General and Efficient Method To Convert Selenides into Selenones by Using HOF·CH3CN. Issue 25 (24th July 2013) - Potash, Shay; Rozen, Shlomo
Abstract: A general route for the preparation of selenones (R2 SeO2 ) is presented. This task is achieved through the quick and high‐yielding reaction of selenides (R2 Se) with HOF· CH3 CN. The reaction tolerates some elusive electron‐deficient and sterically hindered selenides. Some mechanistic aspects are also investigated and discussed. Abstract : A very efficient and general method for the oxidation of selenides (R2 Se) to the corresponding selenones (R2 SeO2 ) is presented. The mild conditions characteristic to HOF· CH3 CN, one of the best oxygen transfer agents available, made it possible for the first time to prepare some sterically hindered and electron‐deficient selenones. Some mechanistic aspects are also investigated and described.